Saccade metrics reflect decision-making dynamics during urgent choices - Joshua A. Seideman (Nature Portfolio, 2018)
Saccades have been extensively used to report choices in perceptual decision making studies yet little is known about the influence of covert decision-related processes on saccade metrics. Here, the authors demonstrate that saccade kinematics is a reliable tell about the degree of decision certainty.